Receptor Binding Domain-Specific B Cell Memory Responses Among Individuals Vaccinated Against SARS-CoV-2 - Atharv Athavale; Anmol Gaur; Nafees Ahmed; Adarsh Subramaniam; Jyotsna Dandotiya; Sneha Raj; Santosh Kumar Upadhyay; Sweety Samal; Anil Kumar Pandey; Ramesh Chandra Rai; Amit Awasthi (Vaccines)
Background: The COVID-19 pandemic prompted unprecedented vaccine development efforts against SARS-CoV-2. India, which was one of the countries most impacted by COVID-19, developed its indigenous vaccine in addition to utilizing the ones developed by other countries. While antibody levels and neutralizing antibody titres are considered initial correlates of immune protection, long-term protection from the pathogen relies on memory B and T cells and their recall responses. In this regard, global research has primarily focused on mRNA-based vaccines. The studies on immune memory response, particularly B cell memory response induced by the vaccines given to Indians, remain relatively obscure. Methods: We assessed Receptor Binding Domain-specific memory B cells in the peripheral circulation and their ability to secrete antigen-specific antibodies among Indians vaccinated with Covaxin (BBV152), Covishield (AZD1222), Corbevax (BECOV2D), and Sputnik Light, as well as unvaccinated individuals. Results: Corbevax and Sputnik Light conferred better antibody-secreting cell (ASC) responses over time compared to other groups. Conclusions: These findings contribute to our understanding of vaccine-induced immune memory in the Indian population; providing insights that could inform future vaccine strategies.